Natural law theory and constitutional construction in the United States - Holovko, O. M. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2016)
The article is devoted to historical and legal analyze of the problem of mankind transition to a constitutionalism. It was the constitutional process in USA. It was a first time of constitutional building based on the democratic values, equality, promotion of human rights. The specific of USA statement’s organization is showed. It was proven the importance of the natural law theory for becoming of modern western constitutionalism’s practice. An attentive was accented on the importance of promotion of human rights in modern world, in all states.